Block channel equalization in the presence of a cochannel interferent signal. - Ginesi, A.
Novel algorithms for block equalization of M-ary phase shift keying (PSK) signals transmitted over multipath fading channels in the presence of an interferent cochannel signal are introduced and analyzed. The algorithms exploit the intrinsic statistical properties of cochannel interference (CCI) in order to mitigate its effects. Both linear and decision feedback equalizers (DFEs) are derived under the assumption that the overall channel impulse responses of both the useful and the inteferent signal are known. Simulation results show that: (a) whereas zero-forcing block equalizers yield a large noise enhancement effect, a minimum mean-square block DFE (MMSE-BDFE) can efficiently compensate for the distortion in the useful channel and reduce the effect of CCI at the same time, and (b) the MMSE-BDFEs outperform conventional DFEs, at least in the idealized conditions of our analysis
Keywords: CCI; FDMA; ISI; M-ary phase shift keying; MMSE-BDFE.; MPSK signals; TDMA; Block channel equalization; Block equalization algorithms; Cellular radio systems; Channel distortion compensation; Channel impulse response; Cochannel interference signal; Decision feedback equalizer; Interference suppression; Intersymbol interference; Linear feedback equalizer; Minimum mean-square block DFE; Noise enhancement effect; Simulation results; Statistical properties; Useful channel; Zero-forcing block equalizers